Gerodietic meat products technology - Galenko, Oleg (My University, 2019)
The results of previous physicochemical and organoleptic investigations showed that bone paste can be used in the food industry. The investigation of the microstructure of sausage meat and finished boiled sausages produced using model receipts, shows that addition more than 15% of utritional supplement to the content of the product results in powdery structure of finished sausages. It is proved that the optimal amount of the bone paste in finished product is 10%. Результати попередніх фізико-хімічних та органолептичних досліджень показали, що кісткова паста може використовуватися в харчовій промисловості. Дослідження мікроструктури ковбасного м’яса та готових варених ковбас, виготовлених із використанням модельних рецептур, показує, що додавання понад 15% введених добавок до вмісту продукту призводить до порошкоподібної структури готових ковбас. Доведено, що оптимальна кількість пасти в готовому продукті становить 10%.
Keywords: gerodietic; meat products; supplements; геродиєтичні; м’ясні продукти; добавки; кафедра технології м’яса і м’ясних продуктів